Emotional and Rational Appeals Influence on Purchase Intention of Airasia Products : Implicit and Explicit Memory as Mediator Variables - Mohamad Asyraaf, Mohamad Attan; Janifer, Lunyai; Norazirah, Ayob; Mohd Waliuddin, Mohd Razali (Human Resource Management Academic Research Society (HRMARS), 2023)
Online advertising is becoming an integral part of business elements. In the past, the use oftraditional media such as newspaper and television advertisements was normal. However, inthese past few years, it is becoming increasingly normal for advertisers to use non-traditionalmedia such as social media namely Facebook, You Tube, Instagram and TikTok, to name a fewto promote their products. Advertisers wanted their customers to remember, recognise andrecall their brands by using advertisements of different advertising appeals. Our brain,meanwhile, plays an important role for us to remember, recognise and recall thingshappening in our daily lives. That includes memorising, recognising and recalling brands thatwe saw before we decided whether to buy or not to buy the products we saw. In recentstudies on advertising appeals, there is less number of papers understanding the relationshipbetween emotional and rational appeals and purchase intention, mediated by implicit andexplicit memory. This paper will aim to understand the relationship between both emotionaland rational appeals and purchase intention with implicit and explicit memory as a mediator